2017
DOI: 10.1038/s41598-017-02727-8
|View full text |Cite
|
Sign up to set email alerts
|

A high-throughput assay for quantitative measurement of PCR errors

Abstract: The accuracy with which DNA polymerase can replicate a template DNA sequence is an extremely important property that can vary by an order of magnitude from one enzyme to another. The rate of nucleotide misincorporation is shaped by multiple factors, including PCR conditions and proofreading capabilities, and proper assessment of polymerase error rate is essential for a wide range of sensitive PCR-based assays. In this paper, we describe a method for studying polymerase errors with exceptional resolution, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 32 publications
(51 reference statements)
7
30
0
Order By: Relevance
“…Background errors are sensitive to enrichment chemistry and DNA polymerase. The error pattern we observed in QIAseq DNA panels agrees with that in other PCR enrichment studies [25, 26] but differs from hybridization capture studies [6, 22] where A>C and G > T errors are dominant. Also, certain high-fidelity DNA polymerases have been shown to generate tens- or hundreds-fold lower error rates [25].…”
Section: Methodssupporting
confidence: 85%
See 1 more Smart Citation
“…Background errors are sensitive to enrichment chemistry and DNA polymerase. The error pattern we observed in QIAseq DNA panels agrees with that in other PCR enrichment studies [25, 26] but differs from hybridization capture studies [6, 22] where A>C and G > T errors are dominant. Also, certain high-fidelity DNA polymerases have been shown to generate tens- or hundreds-fold lower error rates [25].…”
Section: Methodssupporting
confidence: 85%
“…4 because it is unfair to compare MAGERI with smCounter2 using QIAseq data. MAGERI’s error model is based only on primer extension assays from a mix of DNA polymerases including several high-fidelity enzymes [26], while smCounter2’s error model is specific to the entire QIAseq targeted DNA panel workflow, including DNA fragmentation, end repair and PCR enrichment steps. Because the MAGERI error model does not include errors introduced at the typical DNA fragmentation and end repair process (their assays do not have those steps), MAGERI’s background error rates are lower than those in smCounter2.…”
Section: Resultsmentioning
confidence: 99%
“…The main substitution types of our stereotypical variants were C > T/G > A, C > A/G > T, and A > G/T > C (71.05%, Fig. 4c), which were consistent with the substitution types from Oncosmart3 RSDs (Table S2-4) and previously reported error profiles for 'Kapa HF' polymerase [43]. The percentage of these six substitutions further increased to 84.297% in 121 shared sites, which demonstrated that these substitutions introduced by PCR errors were likely to occur universally (Fig.…”
Section: Characteristics Of Mutant-family-level Noisesupporting
confidence: 88%
“…Additionally, after polishing based on Oncosmart2, no stereotypical noises were found among the 5 Oncosmart3 RSDs at the intersection region of the two panels (Table S2-2). Stereotypical noise is caused by many factors, such as DNA damage [42] and PCR errors [43], which have different substitution preferences. The main substitution types of our stereotypical variants were C > T/G > A, C > A/G > T, and A > G/T > C (71.05%, Fig.…”
Section: Characteristics Of Mutant-family-level Noisementioning
confidence: 99%
“…For TCR-Seq datasets, TCR sequences were randomly selected from the pool and assigned with corresponding abundances to mimic the heavy-tailed distribution of TCR sequences in real situations, which satisfied the Zipf distribution with the parameter of α = 3(Bolkhovskaya et al 2014). To simulate the errors introduced by PCR amplification in the library preparation procedure of TCR-Seq, selected TCR sequences were amplified approximately 18 times, with a reaction rate of − 1 and a substitution error rate of 2 × 10 −5(Shagin et al 2017), where follows a normal distribution (E = 1.90, D = 0.1)(Karlen et al 2007). ART(Huang et al 2012) was then used to simulate paired-end reads of Illumina HiSeq 2500 (default error profiles provided by ART) on DNA libraries (mean fragment length 300 bp, standard deviation 100 bp) with different read lengths (75, 100, and 150 bp) and different library sizes (5, 10, and 15 M reads).…”
mentioning
confidence: 99%